GENDER DIFFERENCES AND MORPHOLOGICAL VARIATIONS IN THE EXTERNAL EARS OF YOUNGER ADULTS IN BANGALORE CITY: A PILOT STUDY (Journal of Forensic Medicine & Toxicology, 2023)
The external human ear is a morphologically complex structure and plays a significant role in gathering environmental sound. Forensic anthropologists can analyze variations and establish the use of the ear as a biometric by using information regarding its diverse morphological characteristics in healthy individuals. The current research attempts to ascertain gender differences and morphological variation in the ear print characteristics of the Bangalore population. 130 young adults (58 males and 72 females) aged between 18 to 25 residing in Bangalore were considered for the study through purposive sampling technique. Participants were made to paste their ears slowly and lightly on the glass smeared with printer’s ink and then transferred to the specified space on the A4-sized (70gsm) paper. Ear indices such as ear length, ear width, lobule length, and lobule width from both ears were measured three times in succession, and the mean value was considered. The present study suggests that the oval ear predominated in male and female participants, followed by a rounded shape. The Chi-square test for independence indicates a very high association between gender and the left ear shape with a moderate effect size, and an association exists between gender and the right ear shape with a moderate effect size. The Chi-square test of independence demonstrated an association between ear shape and gender for both sexes and the independent sample t-test implies a significant difference in the features of the left and right ears in male and female participants. These findings will cater to ear print identification, individualization, and classification.
Keywords: Forensic Anthropology; Ear Print; Bangalore; Gender differences; Chi-Square test